Les tiers-lieux de l'école : des espaces d'expression de l'amitié et du bien-être des enfants. - Sophie Levrard
Our text proposes to answer the following question: how do relationships between children reveal themselves in particular in third-places? In what way do third places prove to be spaces of expression for the well-being of children? Our research focuses on two contributing sciences - the sociology of childhood and social geography - to shed light on children's views on their social relationships in school spaces. To be interested in the issues inherent in school spaces is to try to understand the reciprocal effects between the structure of the school and the socialization processes put in place by the children to achieve subjective well-being. The peer group is a constant reference point in the child's life at school, especially in third-places, namely in spaces that are neither academic nor exclusively recreational from the point of view of adults. Resulting from a long immersion in a school in a rural environment, our ethnographic qualitative survey methodology crosses different tools and makes it possible to grasp the systems of relationships set up by the children themselves. Thus to find alternatives to difficult situations likely to evoke ill-being at school such as loneliness, school work, conflicting relationships with adults or peers, children invest in specific spaces, called third-places, in which imagination, playful and transgression practices are at the heart of children's relationships.